2011
DOI: 10.1055/s-0030-1249649
|View full text |Cite
|
Sign up to set email alerts
|

Stalking and Health - An Austrian Prevalence Study

Abstract: The prevalences found in this study are in line with other international studies, although, in a direct comparison, they are in the lower range. However, these data document the relevance of the phenomenon of stalking for the female Austrian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…Budd and Mattinson (2000), for instance, found that students and singles had a particularly high victimization risk, whereas married people, for example, had a lower risk of becoming a victim of stalking. Similarly, in a study by Basile et al (2006), unmarried, separated and divorced respondents reported higher victimization rates (also see Freidl et al, 2011;Van der Aa and Kunst, 2009). The authors of the FRA study found that single mothers (34 percent) were at an exceptionally high risk of stalking victimization and explained this conspicuousness with the high proportion of previous partners among the offenders.…”
Section: Characteristics and Prevalence Of Stalkingmentioning
confidence: 84%
See 3 more Smart Citations
“…Budd and Mattinson (2000), for instance, found that students and singles had a particularly high victimization risk, whereas married people, for example, had a lower risk of becoming a victim of stalking. Similarly, in a study by Basile et al (2006), unmarried, separated and divorced respondents reported higher victimization rates (also see Freidl et al, 2011;Van der Aa and Kunst, 2009). The authors of the FRA study found that single mothers (34 percent) were at an exceptionally high risk of stalking victimization and explained this conspicuousness with the high proportion of previous partners among the offenders.…”
Section: Characteristics and Prevalence Of Stalkingmentioning
confidence: 84%
“…First, one should take into account that the sample was restricted to the German population aged 16–40 years. Several studies have found that the risk of stalking victimization is age dependent (for example, FRA, 2014; Freidl et al, 2011; Scottish Government, 2014). However, since younger people in particular have been reported to be at a higher risk of experiencing stalking, the main potential risk group of stalking victims was covered in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike in some of the countries that criminalised stalking before, this process was not preceded by an empirical analysis to determine the prevalence of stalking victimisation in Spain. The 1998 British Crime Survey (Budd and Mattinson, 1998;Office for National Statistics, 2015) provided data on stalking in England and Wales, as did similar national studies conducted prior to its criminalisation in Germany (Hoffmann, 2006), Italy (Istituto Nazionale di Statistica, 2007), Austria (Freidl et al, 2011), the Netherlands (Van der Aa, 2010), Sweden (Dovelius, Öberg and Holmberg, 2006), Norway (Narud, Friestad and Dahl 2014) and…”
Section: Introductionmentioning
confidence: 99%